Pengembangan Pelaksanaan Pemeriksaan Sumber Daya Manusia Di Pabrik Rokok Grendel - Budi Iriani Yudaningrum (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2020)
This research about Management Audit based on management of HRD at Pabrik Rokok Grendel to find out the effectivity of human resources function in company. This research is also to find weaknesses regarding company’s human resources function so that writer can give recommendation as alternative for weaknesses correction. Writer use descriptive research type with case study approachment. The method to collect the data are from interview, observation and documentation. The method to analyze data is qualitative analysis with comparing three elements of criteria, causes, and effect in human resources function. Based on research result, capabled seven effectif functions of nine functions of human resources. Those are human resources plan, selection, orientation and placement, worker training and developing, work valuation, compensation and retribution, worker relations, worker dismissal. Even thogh, ineffective functions are worker enrollment and careed development. Based on weaknesses assesment of human resources function in PABRIK.Rokok Gendrel, so writer gives recommendation in order to reach effectivity on human resources function management.